Portuguese-speaking men, alcohol consumption and cancer risks: Under the cultural influence of masculinity (Research, Society and Development, 2021)
Objective- To explore the cultural perceptions of masculinity in relation to alcohol consumption and its potential risk of cancer by Portuguese-speaking men. Method- An online anonymous quanti-qualitative survey hosted by the Opinio platform (May 2018-March 2019). Results- Participants living in Brazil, Canada, Portugal and USA (n=184) indicated that alcohol consumption is integrated in men’s cultural identity, primarily as perceived by 89% of Brazilian respondents. The professional occupation reported as most susceptible to alcohol consumption is civil construction (23.2%), 17.5% of respondents reported alcohol as being part of the lives of students, and unemployment or instability at work were reported by 17.5% as reasons for alcohol consumption in men. Thematic analysis was guided by the following themes: Particular practices of alcoholic consumption according to the perception of masculinity in the Portuguese-speaking ethnocultural context; and, Trends in alcohol consumption influenced by ethnocultural origin, social pressure, and response to stressful factors, as potential risk to cancer. Conclusion- Participants recommended widespread availability of research results demonstrating the relationship between alcohol consumption and risk for cancer as a factor in demystifying alcohol use in relation to cancer. Multidisciplinary and joint research between Occupational and Oncology Nursing can redirect preventive cancer policies to men. Future efforts should include actions both at the individual and collective level, with measures to act on risk factors that may increase the risk of cancer.